Operationalization of the best available techniques and best environmental practices in deep seabed mining regime: a regulatory perspective - Xu, Xiangxin; Li, Minghao; Xue, Guifang (Frontiers in Marine Science, 2023)
Best Practices, including Best Available Techniques (BAT) and Best Environmental Practices (BEP), are typically included to provide for or promote particular practices, methods, measures, or standards in respect of the efficient recovery of a resource and the level of environmental protection. Deep seabed mining (DSM) is an activity to obtain mineral resources from the deep sea, which may have certain adverse impacts on the marine environment. International Seabed Authority (ISA), the regulator of DSM activities in the Area authorized by the United Nations Convention on the Law of the Sea (UNCLOS), has introduced those terms in its Mining Code as critical tools for the reduction in environmental risks arising from DSM. Terms that are not included by the UNCLOS, such as BAT and BEP, are commonly invoked, yet often without specification in the regulatory discourse for DSM. In the absence of precise definitions and operational details, the terms BAT and BEP may not be able to function as anticipated in the DSM domain. Against this backdrop, this paper attempts to explore possible means by which the ISA might enable the contractor to operationalize the BAT and BEP, including providing definitions, their placement in the exploitation regulations, and the criteria for its operationalization in the Standards and Guidelines. This paper cites the existing international instruments that incorporate the terms BAT and BEP and takes particular note of DSM into account to highlight specific considerations for their practical implementation for DSM.